Analisis Pengaruh Covid-19 terhadap Indeks Saham Gabungan Indonesia Periode Maret 2020 – Oktober 2020 - Hery Haryanto (YUME : Journal of Management, 2021)
AbstrakStock market index is very be affected any issues. In previous research, it was found that several major issues had a significant effect, such as the environment, disasters, political work and pandemic diseases. The increasing transmission of Covid-19 has had a significant influence on stock markets performance in any countries whole world. Purpose of this research is to find impact of Covid-19 pandemic which is daily case confirmations, number of daily deaths, number of daily recoveries and travel bans on Indonesia Stock Exchange during period March 2020 to October 2020. The results show daily case confirmations, the number of recoveries. and travel bans do not have a significant impact on the Indonesia Stock Exchange. While variable number of covid-19 deaths has a significant effect. Keywords: Covid-19; Daily Case; Daily Health; Travel Bans; IHSG